Building resilience against violent extremism digitally: trialing a new gender-based approach among gamers - Lamphere-Englund, Galen; Wilson, Mike; White, Jessica; Wallner, Claudia; Kowert, Rachel; Kaewbuadee, Nitchakarn; Regeni, Petra; Newhouse, Alex Bradley (Frontiers in Psychology, 2025)
The rise of online gaming as a dominant social and entertainment space has increasingly attracted attention as a potential vector for radicalization to violent extremism. However, given the challenges of completely eradicating harmful content from these vast community spaces, we also need to focus on strengthening the resilience of individuals active there. To effectively build that resilience, we must first define and understand the current state of resilience among gamers, then identify the factors that contribute to it. This article seeks to do that by building upon the mostly offline-focused Building Resilience Against Violent Extremism framework to explore its applicability in the digital environment and specifically within the highly gendered parameters of gaming spaces and experiences. This article builds upon the wider data collection and findings of a project exploring socialization in gaming spaces with a nexus to radicalization through a gender lens.